Transesterification of Jatropha seed oil using potassium loaded on different forms of zeolite Y as catalyst - Montalbo, Kathrina D. (2012)
This study offers develop the catalyst synthesized from a biomass resource, i.e. rice husk, and employ it in the conversion of vegetable oil, such as Jatropha seed oil, to biodiesel. Different forms of zeolite Y were prepared and used as catalyst support. Overall surface areas of the zeolites were high and suitable to be a catalyst support. However, impregnation led to amorphization and collapse of structures of both NH₄Y and KY. The catalytic activities of those zeolites were also found to be very low as compared to 12k/NaY which was determined to be the best catalyst in a previous study. Rice husk silica itself was also utilized as catalyst support due to its availability and ease of extraction process. Comparison of potassium buffer solution (CH₃COOK/CH₃COOH), and potassium acetate (CH₃COOK) as catalyst precursors was also done in both RHS and NaY (with 12 wt% K loading). It was found out that the structure of RHS is not stable. Collapse of its structure and a decrease of overall surface area from 301 to 11 m²/g was observed and with low catalytic activity. On the other hand, better dispersion of potassium and higher catalytic activity can be obtained using CH₃COOK/CH₃COOH mixture. Catalysts with various potassium loading, 9, 10, 11, and 12 wt%, were tested in transesterification of Jatropha seed oil with 11 wt% K/NaY as minimum amount of metal loading that can give complete conversion of Jatropha seed oil to biodiesel (10.3 wt% as obtained in AAS analysis). Several means to prevent leaching such as ultrasound-assisted impregnation and longer during calcinations time were investigated. It was found out that application of ultrasound during impregnation process increases the overall surface area by 11% but the amount of potassium leached out was also increased. In contrast, longer calcinations time decreased the surface area as well as the catalyst leaching.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman.
Keywords: Transesterification; Jatropha; Zeolite catalysts